Endobronchial Mycobacterium avium Infection in an Immunocompetent Patient - Kang, Seung-Hwa (The Korean Society of Infectious Diseases and Korean Society for Chemotherapy, 2013)
Although Mycobacterium avium complex (MAC) is the most common pathogen in nontuberculous mycobacterial (NTM) pulmonary diseases, endobronchial lesions caused by MAC infections are very rare even in an immunocompromised host. Herein, we describe the case of a 59-year-old, HIV-negative and non-immunocompromised woman who developed multifocal pulmonary infiltrations with endobronchial lesion caused by M. avium. Bronchoscopic examination revealed white- and yellow-colored irregular mucosal lesions in the bronchus of the left lingular division. M. avium was identified using sputum culture and bronchial washing fluid culture. Following the recommendations of the American Thoracic Society and Infectious Diseases Society of America (ATS/IDSA), the patient was begun on treatment with antimycobacterial drugs. After treatment, pneumonic infiltration decreased.